2020
DOI: 10.33225/pec/20.78.1000
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate Economics Curriculum and Employability Skills in South Africa

Abstract: Graduates with employability skills are considered as assets by employers because they are dynamic and adapt easily to today’s work environment. Thus, higher education globally is under pressure to produce graduates who are employable and able to continue learning and remain employed. This study examined the extent to which the undergraduate economics curriculum in South Africa equips economics graduates with employability skills. This was achieved through a qualitative approach using a content analysis design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…Not only do soft skills represent a portfolio of attributes, soft skills are also believed to add value to technical hard skills which tend to be habitual, rather than because of "learning by doing" within different particular contexts (Majid et al 2019, 20). Whilst hard skills are focused on in more depth at South African HEIs, many argue that soft skills are equally important component of curricula, as well as providing broader life opportunities for students (Pezer 2021, 62;Boughey and McKenna 2021) -and Ngulube (2020, 1002 has argued that, in some instances, "[South African] employers are more interested in soft skills than hard skills".…”
Section: Higher Education: South Africamentioning
confidence: 99%
“…Not only do soft skills represent a portfolio of attributes, soft skills are also believed to add value to technical hard skills which tend to be habitual, rather than because of "learning by doing" within different particular contexts (Majid et al 2019, 20). Whilst hard skills are focused on in more depth at South African HEIs, many argue that soft skills are equally important component of curricula, as well as providing broader life opportunities for students (Pezer 2021, 62;Boughey and McKenna 2021) -and Ngulube (2020, 1002 has argued that, in some instances, "[South African] employers are more interested in soft skills than hard skills".…”
Section: Higher Education: South Africamentioning
confidence: 99%
“…Recent research findings suggest that getting a degree is just not enough to land a graduate with employment and remain employed (Majid et al, 2020). Ngulube (2020) argued that the twentyfirst century is a knowledge-based economy characterised by the information age which advocates generic skills. Majid et al, (2020) stated that students should therefore be taught how to learn since the work environment is always subject to a variety of uncertainties.…”
Section: Employability Skillsmentioning
confidence: 99%
“…Many agencies and business organisations believe that new graduates are unprepared for the working world (Griffiths et al, 2018;Osmani et al, 2019;Abelha et al, 2020). Studies in the United States ( Rosenberg, Heimler & Morote 2012;Qenani, MacDougall & Sexton 2014), Canada (Finch et al 2013), Australia (Prikshat et al 2020), India (Unni, 2016), Bangladesh (Uddin, 2021), China (Su & Zhang 2015), Malaysia (Fahimirad et al 2019;Kenayathulla et al 2019), the United Kingdom (Azevedo et al 2012;McMurray et al 2016), Germany and Italy (Succi & Canovi 2020), Portugal (Sin & Amaral 2017), South Africa (Ngulube 2020), Mauritius (Hardin-Ramanan et al 2020), Nigeria (Nwajiuba et al 2020;Okolie et al 2020) and Ghana (Damoah et al 2021) have revealed a mismatch between the materials students learned at university and the skills required by the labour market.…”
Section: Introductionmentioning
confidence: 99%